(untitled) (Medical Forum Monthly, 2024)
Medical experts have emphasised the need to create awareness among people about not going to quacks as they are a major source of spreading diseases, including deafness, in people on mass scale. “The government must take stringent action against roadside quacks, who are spreading innumerable diseases, including deafness, among the unsuspecting people,” they said while speaking at a seminar on “21st Century - Deafness is no more an issue” organised by the Mir Khalil-ur-Rahman Memorial Society (Jang Group of Newspapers) in collaboration with the Deafness Foundation of Pakistan here at a local hotel the other day. Speaking on the occasion, Deafness Foundation of Pakistan Chairman and ENT specialist Dr Nasrullah Rana said people should neither visit quacks nor resort to self-medication specially in case of hearing loss and he advised them to only go to qualified consultants for their treatment in this regard. He also pointed out that people had mistaken ear wax as ear filth and tried to remove it through various means, which might cause deafness, adding that ear wax was actually guard against deafness and prevents hearing loss. “Cotton bud, match-stick, hair-pin and keys should not be used to clean ears,” he advised people and prohibited them from putting oil in ears as well. He also advised people not to slap on the face of children as it could also cause deafness.